2002
DOI: 10.1080/jmf.11.4.270.274
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal effects of magnesium sulfate on serum osmolality in pre-eclampsia

Abstract: High blood pressure in pre-eclampsia is not associated with altered osmolality. An absence of the normal decrease in fetal osmolality is observed in pre-eclamptic women treated with magnesium sulfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Interestingly, MgSO 4 infusion caused significant increases in ionized Mg +2 levels, while serum ionized Ca 2+ concentrations were unchanged [40], suggesting that the effect of MgSO 4 is not exerted through modulations of ionized calcium levels [41]. Also, it was observed that in the normal pregnant women, ionized Ca 2+ levels were higher in foetal blood and that this same condition was found in PE women treated with MgSO 4 [42], suggesting that this treatment has no effect on Ca 2+ transplacental transfer. Characteristics of pregnancies are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, MgSO 4 infusion caused significant increases in ionized Mg +2 levels, while serum ionized Ca 2+ concentrations were unchanged [40], suggesting that the effect of MgSO 4 is not exerted through modulations of ionized calcium levels [41]. Also, it was observed that in the normal pregnant women, ionized Ca 2+ levels were higher in foetal blood and that this same condition was found in PE women treated with MgSO 4 [42], suggesting that this treatment has no effect on Ca 2+ transplacental transfer. Characteristics of pregnancies are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%